Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
m=2
Step-by-step explanation:
to understand this
you need to know about:
- law of exponent
- PEMDAS
given:
- [tex] \frac{ {5}^{m} }{ {5}^{ - 3} } = {5}^{5} [/tex]
tips and formulas:
- [tex] \frac{ {x}^{a} }{ {x}^{b} } = {x}^{a - b} [/tex]
- [tex] {x}^{a} = {x}^{b} < = > a = b[/tex]
let's solve:
[tex] \frac{ {5}^{m} }{ {5}^{ - 3} } = {5}^{5} [/tex]
[tex] {5}^{m - ( - 3)} = {5}^{5} [/tex]
[tex]m + 3 = 5[/tex]
[tex]m = 2[/tex]
Answer:
[tex] {5}^{m} \div {5}^{ (- 3)} = {5}^{5} \\ {5}^{m} \div \frac{1}{ {5}^{3} }= {5}^{5} \\ {5}^{m} \times {5}^{3} = {5}^{5} \\ {5}^{m} = \frac{ {5}^{5} }{ {5}^{3} } \\ {5}^{m} = {5}^{2} \\ \boxed{m = 2}[/tex]
★ m=2 is the right answer.
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.